Focal Peritoneal Mesothelioma Demonstrated on FDG PET/CT. (November 2019) - Xiao, Jie; Yin, Hongyan; Cheng, Dengfeng; Shi, Hongcheng; Xiu, Yan
Abstract : Abstract: A 48-year-old woman was experiencing abdominal pain and melena for 3 months. Because of these symptoms combined with increased level of tumor marker CA125, possible abdominal malignancy was considered, and an FDG PET/CT was performed to assess occult tumor. The images revealed multiple hypermetabolic lesions along the peritoneal surface. Pathological examination after biopsy demonstrated low-grade epithelioid peritoneal mesothelioma.